Factorise (1+3y)^2 +(9y^2-1)
Answers
Answered by
83
Answer:
hey mate
(1+3y)²+(9y²-1)=((1)²+(3y)²+2×1×3y)+ (9y²-1)
=(1+9y²+6y) + (9y²-1)
=1+9y²+6y+9y²-1
= 18y²+6y
using identity ...
(a+b)= a²+b²+2ab
hope it will help you
Answered by
5
Given :
To find : To factorise
Solution :
Step 1 of 3 :
Write down the given expression
The given expression is
Step 2 of 3 :
Simplify the given expression
Step 3 of 3 :
Factorise the expression
━━━━━━━━━━━━━━━━
Learn more from Brainly :-
how many terms are there in an expression 12ab -24b +36a
https://brainly.in/question/22764723
2. On common factorization 12a+9 becomes 3a(4a+3)
https://brainly.in/question/30544360
3. Solve the equation 12p-11=25
https://brainly.in/question/26811798
Similar questions